2019
DOI: 10.1002/ange.201906416
|View full text |Cite
|
Sign up to set email alerts
|

Direct Z‐Scheme Hetero‐phase Junction of Black/Red Phosphorus for Photocatalytic Water Splitting

Abstract: Blackphosphorus (BP) has recently drawn attention in photocatalysis for its optical properties.However,limited by the rapid recombination of photogenerated carriers,the use of BP for photocatalytic water splitting still remains ah uge challenge.H erein, we prepare ab lack/red phosphorus (BP/ RP) hetero-phase junction photocatalyst by aw et-chemistry method to promote the interfacial charge separation and thus achieve Z-scheme photocatalytic water splitting without using sacrificial agents.The Z-scheme mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 47 publications
2
62
0
Order By: Relevance
“…According to the date from UPS, the work function ( Φ , difference between the Fermi and vacuum level) and E VBM (VB energy) can be calculated by previous report. [ 24 ] Figure 4C shows the UPS spectra of CdS and Mo 2 C. The ϕ s of CdS and Mo 2 C were calculated of −4.04 and −4.56 eV, indicating CdS and Mo 2 C should be a reduction‐type photocatalyst (with higher Fermi level and smaller work function) and an oxidation‐type photocatalyst (with lower Fermi level and larger work function), respectively. The VB energies ( E VB ) of CdS and Mo 2 C were calculated to be −5.74 and −6.18 eV (vs vacuum), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…According to the date from UPS, the work function ( Φ , difference between the Fermi and vacuum level) and E VBM (VB energy) can be calculated by previous report. [ 24 ] Figure 4C shows the UPS spectra of CdS and Mo 2 C. The ϕ s of CdS and Mo 2 C were calculated of −4.04 and −4.56 eV, indicating CdS and Mo 2 C should be a reduction‐type photocatalyst (with higher Fermi level and smaller work function) and an oxidation‐type photocatalyst (with lower Fermi level and larger work function), respectively. The VB energies ( E VB ) of CdS and Mo 2 C were calculated to be −5.74 and −6.18 eV (vs vacuum), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In order to effectively catalyze CO 2 reduction, various photocatalysts had been investigated and developed [7][8][9] . In pre-vious works [10][11][12] , most of high-efficiency photocatalysts of CO 2 reduction contained metal elements, which were expensive and environmentally harmful.…”
Section: Introductionmentioning
confidence: 99%
“…14 Liu et al reported that synthesis of composite of BP/RP with high photocatalytic activity for water splitting from RP in amine solvent. 15 However, there are few reports on method to get high yield of BP and the synthesis mechanism of BP from RP were unclear.…”
Section: Introductionmentioning
confidence: 99%